Study protocol: Comparison of the effect of treatment with Nonsteroidal anti-inflammatory drugs added to anti-tumour necrosis factor a therapy versus anti-tumour necrosis factor a therapy alone on progression of Structural damage in the spine over two years in patients with ankyLosing spondylitis (CONSUL) – an open-label randomized controlled multicenter trial. Issue 6 (10th June 2017) - Proft, Fabian; Muche, Burkhard; Listing, Joachim; Rios-Rodriguez, Valeria; Sieper, Joachim; Poddubnyy, Denis
Abstract : Introduction: There is some evidence that non-steroidal anti-inflammatory drugs (NSAIDs), in particular celecoxib, might possess not only a symptomatic efficacy but also disease-modifying properties in ankylosing spondylitis (AS), retarding the progression of structural damage in the spine if taken continuously. In contrast, this remains controversial for tumour necrosis factor alpha (TNF-α) inhibitors, despite their good clinical efficacy. The impact of a combined therapy (a TNF inhibitor plus an NSAID) on radiographic spinal progression in AS is unclear. Methods and analysis: The aim of this study is to evaluate the impact of treatment with an NSAID (celecoxib) when added to a TNF inhibitor (golimumab) compared with TNF inhibitor (golimumab) alone on progression of structural damage in the spine over 2 years in patients with AS. The study consists of a 6-week screening period, a 12-week period (phase I: run-in phase) of treatment with golimumab for all subjects followed by a 96-week controlled treatment period (phase II: core phase) with golimumab plus celecoxib versus golimumab alone, and a safety follow-up period of 4 weeks. At week 108, the primary study endpoint radiographic spinal progression (as assessed by the change in the modified Stoke Ankylosing Spondylitis Spine Score after 2 years) will be evaluated. Ethics and dissemination: The study will be performed according to the principles of good clinical practice and the German drug law. The written approval of the independent ethics committee and of the German federal authority have been obtained. On study completion, results are expected to be published in a peer-reviewed journal. Trial registration number: ClinicalTrials.gov register (NCT02758782 ) and European Union Clinical Trials Register (EudraCT No 2016-000615-33).